3(2x+9)=4(x+11)

Simple and best practice solution for 3(2x+9)=4(x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+9)=4(x+11) equation:


Simplifying
3(2x + 9) = 4(x + 11)

Reorder the terms:
3(9 + 2x) = 4(x + 11)
(9 * 3 + 2x * 3) = 4(x + 11)
(27 + 6x) = 4(x + 11)

Reorder the terms:
27 + 6x = 4(11 + x)
27 + 6x = (11 * 4 + x * 4)
27 + 6x = (44 + 4x)

Solving
27 + 6x = 44 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
27 + 6x + -4x = 44 + 4x + -4x

Combine like terms: 6x + -4x = 2x
27 + 2x = 44 + 4x + -4x

Combine like terms: 4x + -4x = 0
27 + 2x = 44 + 0
27 + 2x = 44

Add '-27' to each side of the equation.
27 + -27 + 2x = 44 + -27

Combine like terms: 27 + -27 = 0
0 + 2x = 44 + -27
2x = 44 + -27

Combine like terms: 44 + -27 = 17
2x = 17

Divide each side by '2'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| -8u-19=-5u+11 | | t(4)=32 | | 2v-15=7v-5 | | 2=1.16x+x | | -7v-4=4v+18 | | 2z+20=5z-7 | | e^3=5-2x | | 5w-7=9w+9 | | 3(4x+4)+(-50x)-9(-8-x)= | | 2w-14=7w+1 | | 5x2/3-3x1/3 | | 2w+3=4w+2 | | 1/2(x-4)=2(x+2) | | -9v-4=-v-12 | | 2x^2-19+9=0 | | 4t-18=-t-13 | | 4t-18=-3-13 | | 4b+5=19 | | 9v+19=7v+5 | | 5m+m=132 | | 4z-3=-3z-3 | | x-8.6=3.2 | | 10-7lnx=-4 | | r-7/9=20/9 | | u/3-10=-14 | | 3x(x+7)=36 | | 9+24=3x | | 2x^3+x^2+7=-3 | | (2x^2y^3)^2(-4x^4)^3/(xy)4x^6y^3)^4 | | 15/55 | | 3x+4y+5x-3y= | | g(x)=4x^2-48x+7 |

Equations solver categories